(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Association rule mining is one of the most important data mining problems. The purpose of association rule mining is the discovery of association relationship among a set of items. The mining of association rule include two sub problems (1) finding all frequent Item-sets that appear more often than a minimum support threshold and (2) generate association rules using these frequent Item-sets. The first subproblem plays an important role in association rules mining. This paper provides an overview on the design of frequent pattern mining algorithms